CORRELATES ASSOCIATED WITH ADHERENCE AMONG FEMALE SEX WORKERS ON HIV PRE- EXPOSURE PROPHYLAXIS IN NAIROBI CITY COUNTY, KENYA - Litiema, Edith; Orago, Alloys; Muia, Daniel (Journal of Health, Medicine and Nursing, 2021)
Purpose: The main aim of the study was to assess correlates associated adherence among Female Sex Workers on PrEP in the study. This was done through determining level of knowledge on PrEP, level of adherence, correlates affecting adherence and analysis of strategies to enhancing PrEP adherence. Materials and Methods: A cross sectional analytical study with mixed method using both qualitative and quantitative data collection method was carried out between March and May 2021. Three hundred and forty-five Female Sex Workers (FSWs) were enrolled in the study. Data was collected using structured questionnaire from study participants after having their consent. Three focus group discussions (FGD) were conducted for those FSWs who will not be involved in the quantitative arm of study. Key Informant Interview was conducted with service providers using Key informant interview (KII) guide. Data collected was entered into Excel spread sheet in password protect computer. Data analysis was carried out in, Univariate analysis, bivariate analysis and multivariate analysis. Statistical Package of Social Science (SPSS) version 20.0 was used for analysis. Data was presented using graphs and Tables. Results: The study found that 72% did not know the name of PrEP, 39% reported to have missed PrEP with 33% having missed appointment for PrEP refill. Qualitative data showed that PrEP engagement meetings should be conducted monthly to enhance PrEP adherence. The respondents who had reminders on when to take medication was as well associated with adherence (p=0.014) compared with those not using reminders. The study also found out that employment status was associated with adherence to PrEP medication (P=0.050) with FSW who were salaried being 2.5 times more likely to adhere to PrEP medication compared to those who were not salaried. Unique contribution to theory, practice and policy: The Ministry of Health should ensure that targeted PrEP counselling is done during the initiation for the eligible clients. The information and telecommunication department to work on SMS reminder system in order to remind FSWs using PrEP about appointment dates for the pill pick up thus enhance adherence to FSWs using PrEP. The procurement department should work together with pharmacy department to ensure that there is enough stock for PrEP at every clinic. This will help to ensure that adherence is achieved for the FSWs on PrEP.